An examination of selected works for percussion: Prelúdio No. 1 Mi Menor (E Minor), op. 11 by Ney Rosauro, Prelúdio No. 2 la maior (a minor) by Ney Rosauro, Rotation IV by Eric Sammut, Water Falls for a Desert by Greg Coffey, Strands of Time by Brian Blume, Surface Tension by Dave Hollinden, bitsmoke by Casey Farina - Coffey, Gregory Peter (Kansas State University, 2012)
This is a report intended for musicians and scholars who seek to enhance their understanding of any number of the following compositions: Prelúdio No. 1 Mi Menor (E Minor), op. 11 by Ney Rosauro, Prelúdio No. 2 la maior (A minor) by Ney Rosauro, Rotation IV by Eric Sammut, Water Falls for a Desert by Greg Coffey, Strands of Time by Brian Blume, Surface Tension by Dave Hollinden, bitsmoke by Casey Farina. Each work has been analyzed examined in accordance with Jan LaRue’s Guidelines For Style Analysis. For some compositions including only relative-pitch instruments, analysis of harmony has been omitted. For all compositions, the author has added notable performance considerations, essential technical and interpretive considerations in accord with LaRue’s guidelines. Therefore, the approach taken in analytical categories of this document can be exhibited as Sound, Harmony, Melody, Rhythm, Growth, and Performance.
Keywords: Ney Rosauro; Greg Coffey; Brian Blume; Casey Farina; Dave Hollinden; Eric Sammut; Music (0413)